Democratic innovations after the post-democratic turn: between activation and empowerment. Issue 2 (3rd April 2021) - Hammond, Marit
ABSTRACT: When it comes to the status of democracy, the current times present a curious chasm: On the one hand, the depoliticization of contemporary discourses and institutions has led to both the diagnosis of a factual 'post-democracy' and a normative legitimacy crisis of democracy; yet on the other, there has been a resurgence of normative democratic ideals and practical 'democratic innovations' in the sphere of civil society. This article evaluates the potential of these innovations to engender a genuine renewal of democracy. I find that, despite their emancipatory underpinnings, most participatory and deliberative innovations fit a description of (mere) citizen activation – an elite-led engineering of citizen engagement that, beyond the control of citizens themselves, not only fails to lead to empowerment, but can even work to perpetuate existing structures. In recognition of the ambivalent nature of the post-democratic condition, I argue academics and democratic practitioners must accept a new, more responsive role in relation to citizens and the wider society.